Konflik Batin Tokoh Rinai dalam Novel Rinai, Tinjauan Psikologi Sastra dan Implementasinya Pada Pembelajaran Sastra di SMK - Wijayanti, Ratih Sari Sugeng, Drs. Adyana Sunanda, M.Pd (2017)
The aims of this research are to (1) describe the structure of Rinai novel from Sinta Yudisia, (2) describe the figure internal conflicts of Rinai figures on Rinai novel from inta Yudisia by literary psychology approach, (3) determine the form of the its implementation for learning of Vocational high School. The method of this research which is used is the descriptive-qualitative. The data used in the study is the phrase, sentence, and paragraph relating to thestructure of the novel builders and inner conflicts Rinai character in the novel Rinai Yudisia Sinta work. Sources of primary data in this study is novel Rinai Yudisia Shinta work, secondary data sources such as scientific journals, relevant articles related to builders novel structure and inner conflict the main character in the novel. Researchers collected data by using the techniques of literature, see, record, and interviews. Data analysis techniques in this study is the semiotic techniques include heuristic and hermeneutic reading. Based on the results as follows. (1) Analysis of the structure of the novel Rinai Yudisia Sprott work focused on: the theme, the facts of the story, and literary devices. (2) the inner conflict of the novel Rinai there are four types of conflict. Such conflicts include a) conflict-approaching closer. b) the inner conflict closer-away. c) conflict away-away. d) approaching conflict-away double. (3) The results of this study can be implementatiot into learning in vocational especially Sastra class XII. Keywords: Internal Conflict Figure, Novel Rinai, Psychology approach, Literature Learning in Vocational School